Performance of posterior third-generation monolithic zirconia crowns in a complete digital workflow: A three-year prospective clinical study - Mustafa Gseibat; Pablo Sevilla; Carlos Lopez-Suarez; Veronica Rodriguez; Jesus Pelaez; Maria J. Suarez (Elsevier, 2024)
Background/purpose: Translucent monolithic zirconia restorations have recently introduced. The purpose of this study was to evaluate the clinical behavior and the survival rate of the posterior third-generation monolithic zirconia crowns (MZCs) during three years of clinical service. Materials and methods: Twenty-four patients who needed thirty crowns were enrolled in this study. Digital impressions were made, and the crowns were milled and cemented with a resin cement. The crowns outcomes were assessed using the California Dental Association's (CDA) criteria. Gingival index (GI), plaque index (PI), and periodontal probing depth (PPD) for MZCs and contralateral natural teeth (control) were assessed. Margin index (MI) for MZCs was also assessed. Data analysis was conducted using the Wilcoxon signed-rank and the Friedman tests. Results: The 3-year survival rate was 100%. All MZCs were rated as satisfactory throughout the follow-up period, and no biological or mechanical complications were observed. No differences were recorded when GI, PI and PPD at 3-year of follow-up were compared to baseline. No differences were recorded between crowned and control teeth. The MI remained stable throughout the study period. Conclusion: The third-generation monolithic zirconia appears to be a good treatment option for the rehabilitation of posterior single teeth.